(untitled) (Journal of Applied Business and Economics, 2019)
This study examines the direct and indirect effect of board characteristics on shareholders’ wealth of manufacturing companies in Nigeria using dividend policy as mediator. Study population is six three manufacturing companies listed on the Nigerian stock exchange in 2008 to 2018. Sample of Fifty-one companies were used. Using path analysis, significant impact of dividend payout on BX and SW exist. BC, BS, and BG have positive significant effect on SW (EPS and MPS). It’s concluded that, board characteristics can improve shareholders wealth by using dividend policy. Therefore, sampled firms can restructure their dividend policies for the improvement of shareholders’ wealth.